Ortner syndrome - Girardi, Fabio Muradás; Ardenghi, Rodrigo Machado (Clinical and Biomedical Research, 2020)
Inferior laryngeal nerve palsy is a relatively common entity. Nevertheless, an occurrence as a result of a cardiovascular pathology is rare. In this case, it is called Ortner’s syndrome (OS). Aortic diseases are responsible for more than a half of cases. Supraaortic vessels disorders are rare causes of OS. In our new report, a non smoker and non alcohol drinker 70-year-old woman presented with a history of dysphonia since her childhood. On direct laryngoscopy, a left vocal cord paralysis was detected. A contrast enhanced Computed tomography showed on an aberrant right subclavian artery, originating from the left portion of the aortic arch. Its course to its usual site runs behind the esophagus, being also called arteria lusoria. In this particular case, two unusual situations appear together, which contributes to the rarity of the event.